Mental Health Of Occupational Therapy Students And The Academic Environment (Revista Contexto & Saúde, 2020)
ABSTRACTIt is perceived that in graduation for great changes, marked by individual and collective experiences, implying greater responsibility, sociability, appropriateness as norms, methodologies, groups and unknown people, which can become stressing and ill being factors. Objectives: To analyze the influence of the environment on mental health and its reflexes in the occupational space of the Occupational Therapy Students of the University of the Amazon. Method: The research was qualitative, of the type of Multiple Case Study, descriptive, transversal, field and prospective. The media has been used by the researchers, called "Mental of the students", that has resources of self-evaluation of mental state, institutional evaluation and four subjective questions, carried out with 4 students of Occupational Therapy of UNAMA. Results: All respondents identify themselves as anxious, dissatisfied and with physical exhaustion. The responses point to the impairment of Sleep and Sleep performance. Listening the main causes: difficulty in managing time, constant constant, can not be enjoyed at night, and permanent monitoring in activities that are performed the day after. In addition, they were cited as Leisure and Social Participation occupations. Conclusion: The academic environment presents stressful factors, which the individual does not have intense contact. And that, when you have your commitments, you have your nutritional changes, especially Rest and Sleep, in addition, stay alert, concentration and assiduity and a difficulty in adapting to a nervous process of illness. This study is fundamental for social students of mental health university student.
Keywords: Mental Health; Students; Occupational Therapy; Occupational Performance; Universities